The Campus Canopy, 1935-02-27 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1935)
Y.W.C.A. Opens Charm School; Thursday Games Evenly Matched - Lambdas Win Basketball Game - Kappas win First Ball Game; University Council Discusses Training; Sock and Buskin Presents Club Frolic; Assembly Address Features Dr. Pyle; Department Receives New Equipment; Vespers;
Georgia State Womans College. "The Campus Canopy, February 27, 1935." Vol.01, No.11. Valdosta State University Archives and Special Collections, 2018. http://hdl.handle.net/10428/2981. ### Persons Mentioned ### A. C. Pyle; Albert Tuck; Aldine Rosser; Amanda Barksdale; Anne Mary Evans; Annie Kate Knight; Annie P. Hopper; B. Sirmons; Berkley McKey; Bernard Baker; Bessie Lewis; Betty Vaughn; Billy Fisher; Billy Knox; Bo Whittaker; Bobbie Cochran; Brian Ahearne; Broun Hutchinson; Buddy Milner; C. J. Nix; Carl Pittman; Carroll Peeples; Catherine the Great; Chappie Bragg; Charles Dunbar; Charles Hudson; Charles Joyner; Charles Shelton; Christ; Clara Davis Adams; Clement Greene; Cleo Barber; Clyde Carter; Curtis Jackson; D. W. Beaty; Daisy Daniels; Daniel Ash; Dave Sholtz; David Price; Denise Beasley; Doris Swindle; Earl McKinney; Earl Phelan; Ed Jenwright; Edith Bennett; Edwin McCrory; Eleanor Miller; Elizabeth Bergner; Elizabeth McRee; Estelle Roberts; Esther Smith; Ethlyn Massey; Eunice Adams; Florence Tharp; Frank King; Frank Middleton; Gene King; Gertrude Gilmer; Gladys Warren; H. G. Cannon; H. T. McIntosh; Harold Punke; Harriette Radford; Harris Dukes; Harris Perry; Henry Kate Gardner; Henry MacCracken; Herbert Wood; Herman Johnson; Hilton Hutchinson; Hugh Kroell; Hunter Hurst; J. A. Durrenberger; J. Radford; J. T. Holt; Jack Howell; Jack Williams; Jake Roberts; James Howard; Janet Cook; Jeanette Shifrin; Jerry Tullis; Jessie Langdale; Jesus Christ; Jimmy Caraballo; Joe Whipple; John Sineath; Johnnie Mae Kelley; Joseph Newton; Josephine Joubert; L. R. Scott; La Forest Smith; Lawton Ursry; Lee Branch; Lee Pattison; Leila Mae Tyson; Leila Urquhart; Leonora DuFour; Leonora Ivey; Leslie Turner; Lillian Slocumb; Louise Sawyer; Louise Smith; Lucille Holt; Lucille Thompson; Lucille Tyson; Lucy Hammond; Madame Verdevere; Maggie Davidson; Margaret Cannon; Margaret Hudson; Margaret Lindsay; Margaret Zipplies; Marie Miller; Marion Reid; Martha Gardner; Martha Gay; Martiel Lundy; Marvin Hood; Mary Agnes Roane; Mary Askew; Mary Elizabeth; Mayme Register; Melville Brinson; Micky Daniels; Mildred Turnbull; Minnie Ledford; Miriam Adams; Mussolini; Pearl Wilson; Prentice Taylor; Priscilla Kelley; Rachel Coxwell; Rena Mayes Rhodes; Roland Knight; Roy New; Ruth Williams; S. Miller; Sam Brooks; Sherwood Dennis; Tad Whipple; Thad Wiseman; Thomas Neblitt; Tom Swearingen; Una Ritch; Valentine; Vangie Trimble; Vasco Martin; Vernon McRae; Dubislav Gneomar von Natzmer; W. B. Watkins; Walt Williams; Walter Williams; Willene Roberts; Zelda Tucker; Virginia Kirkland; Virginia Tuck; Carlie Bell; Lawrence Tibbett; ### Locations Mentioned ### America; Athens, Georgia; Baxley, Georgia; Cairo, Georgia; Dixie; Emory University; Fitzgerald, Georgia; Gabbettville, Georgia; Georgia; Homerville, Georgia; Idaho; Indiana; Jasper, Florida; Milledgeville, Georgia; Miss Virginia; Pinehurst, Georgia; Quitman, Georgia; Rang Tang Lu Ranch; Ray City, Georgia; Sarasota, Florida; Statesboro, Georgia; Sylvester, Georgia; Thomasville, Georgia; Twin Lakes, Georgia; Valdosta, Georgia; Vassar College; Waycross, Georgia; ### Organizations Mentioned ### Federal Emergency Relief Administration; Georgia State Womans College; Athletic Council; Emory Glee Club; Fine Arts Club; Florida State College for Women; Georgia Press Association; Glee Club; International Relations; Mercer Glee Club; National Rifle Association; Philharmonic Club; Rollins College; United States United States Supreme Court; University Council; Young Women's Christian Association;
Keywords: Georgia State Womans College -- Students -- Periodicals; Newspapers; College student newspapers and periodicals -- Georgia -- Valdosta